The state of functionally reserve possibilities of cardiovascular system of students with different levels of physical activity - Holovchenko O.I; Vostotska I. F.; Osipova І. L. (Kharkov National Pedagogical University, 2012)
Directions of estimation of the state of functionally reserve possibilities of the cardiovascular system of students with the different level of movement activity are considered. Research was conducted among 50 students of pedagogical university of 17-20 years. It was appraised the daily allowance of energy consumption and adaptation possibilities of the cardiovascular system of students. It was found out the reasons of forming of high level of energy consumption for students and direct dependence of energy consumption and bringing in students youth to the educational object «Physical education». Adaptation possibilities of the cardiovascular system of students are answering to the middle level. Dependence of level of the functional state of the cardiovascular system of students is set on age that tendency to connection with the level of movement activity. The age-old dynamics of indexes of frequency of heart-throbs is studied during a functional test with the physical loading. Description of daily allowance energy consumption of students is given at the different regime loadings.